Revisiting Consumer Behavior: Dominant Factors Shaping Consumer Rationality - Joshi, Uttam Lal; Bhusal, Bhim Prasad (International Research Journal of MMC, 2026)
Consumer rationality concerned with the consumer behavior theory plays a significant role in the analysis of economic theories. Since rationality has been mainly influenced by a number of personal and socio-economic factors; age, education, gender, occupation, family size, individual’s income and expenditure, there exists a relationship between rationality and among these factors. To examine whether such a linkage between the factors ensue or not in the developing countries’ markets is the major focus of this study. If such a linkage exists, what are the dominant factors affecting rationality among them is another concern. To this extent, three dimensions – price, quality and brand were taken as the proxies of consumer rationality and data were collected through survey method by sending questionnaires to the respondents. Under the quantitative research design, the logistic regression model was employed to analyze the data. The results showed that all of the explanatory factors used in the system had more or less significant effect on the concerned rationality factors. The estimated results of the three models showed that the effect of education and occupation in all odd ratios was strong, the effect of age and expenditure hindered and nearly no effect of gender, family size and income. Therefore, among the explanatory variables taken in the estimation, education and occupation are the dominant factors in consumer rationality in Nepal. In the case of developing countries, it may have a significant importance to enhance the consumer’s knowledge to the concerned stakeholders, producers, researchers and policy makers in their way of business and living in the present context.